PEMBUATAN BUKU FOTOGRAFI MAKANAN (STUDI KASUS OBYEK MASAKAN JAWA TIMUR) - Putra, Ilham Rizaldi Permadi; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal ArtNouveau, 2013)
The development of photography, especially in Indonesia experienced significant growth, in the sense that photography is not just a professional job but has become a life style for urban communities. This phenomenon can be seen from the increasing number of media that talks about the world of photography, ranging from newspapers, magazines, television, and internet. The purpose of this research is directed at making food photography reference book themed cuisines of East Java. Food Photography food can not be separated from the object. Therefore, this thesis uses the typical food of East Java. Provinces were chosen for the book to be made so that the communicative and able to enter the minds of the public. East Java has several cities, among others, Surabaya, Lamongan, Gersik, Malang, Kediri, Banyuwangi, Madiun, Ponorogo, and Madura, from every city has a food such as rujak cingur, semanggi, lontong balap, kupang lontong, rawon, Nasi pecel, soto ayam, sate ayam, nasi jagung, urapan, kikil, semur lidah, tahu campur, tahu tek, dan nasi krawu. Of the selected food representing cities in East Java because these foods are familiar in peoples hearts.The books which talk about food photography rare version dirak Indonesia - Indonesian shelf bookstalls in the book so terbuatnya lift dishes from East Java in order to attract people and make this book as a medium of publication, documentation, and reference.